Pembuatan Pupuk Kompos berbasis Limbah Rumah Tangga Guna Meningkatkan Kesejahteraan Masyarakat Kelurahan Durian Payung: Making Compost Fertilizer based on Household Waste to Improve the Welfare of the Durian Payung Village Community - Deni Ardiansyah; Novita Sari; Retno Pinarsih; Rossy Meliyana (Experimental Student Experiences, 2022)
This Community Service Program aims to provide insight in finding creative ideas in processing household waste, especially into natural fertilizer. Composting household waste using a composter can help municipal waste management efforts in the form of: reducing the amount of waste generation at the source, reducing transportation costs for waste transportation, and extending the life of the landfill. The method used in this community service activity is carried out in 4 stages, namely observation, preparation, implementation, monitoring and evaluation. Compost that comes from household waste in the form of leftover vegetables and or fruit peels, and EM4 fertilizer is added as a catalyst in making compost. Household waste that no longer has economic value will have useful value when it can be reprocessed into something useful, one of which is compost. The compost produced from this activity is dark brown to black in color similar to the color of the soil, does not dissolve in water and does not smell, so it can be concluded that the quality of the compost produced is quite good.